OCT-Angiography Face Mask–Associated Artifacts During the COVID-19 Pandemic. Issue 6 (23rd June 2022) - El-Nimri, Nevin W.; Micheletti, Eleonora; Mohammadzadeh, Vahid; Nishida, Takashi; Kamalipour, Alireza; Zangwill, Linda M.; Bowd, Christopher; Moghimi, Sasan; Weinreb, Robert N.
Abstract : Précis: Face mask wearing has no significant effects on artifacts or vessel density measurements in optic nerve head (ONH) and macular optical coherence tomography-angiography (OCT-A) scans. Purpose: The aim was to assess the difference in area of artifacts observed in optical OCT-A scans with and without face mask wear and to verify if mask wear interferes with OCT-A vessel density measurements. Subjects and Controls: A total of 64 eyes of 10 healthy subjects, 4 ocular hypertensive, 8 glaucoma suspects, and 17 glaucoma patients were included. Materials and Methods: High-density ONH and macula OCT-A scans were obtained in patients with and without surgical masks. Seven different artifacts (motion, decentration, defocus, shadow, segmentation failure, blink, and Z-offset) were quantitatively evaluated by 2 trained graders. The changes in the area (% of scan area) of artifacts, without and with mask wearing, and differences of vessel density were evaluated. Results: Trends of increasing motion artifact area for the ONH scans [4.23 (−0.52, 8.98) %, P =0.08] and defocus artifact area for the macular scans [1.06 (−0.14, 2.26) %, P =0.08] were found with face mask wear. However, there were no significant differences in the mean % area of any artifacts ( P >0.05 for all). Further, the estimated mean difference in vessel density in images acquired without and with masks was not significant for any type of artifact. Conclusion: Face mask wearing had no significant effect on area of artifacts or vessel density measurements. OCT-A vessel density measurements can be acquired reliably with face mask wear during the pandemic.